Perancangan visual display katalog produk dengan pendekatan ergonomi - Gisella Biaz Advendina; Chandra Dewi Kurnianingtyas (Jurnal Teknik Industri dan Manajemen Rekayasa, 2023)
The rapid development of information technology has caused drastic changes in the world in recent decades. One of the information systems that companies need to increase sales is a catalogue. Product catalogues are an effective marketing tool for promoting company products and attracting potential buyers. The purpose of this research is to create a visual catalogue display that is easy to use and efficient for users so that users can quickly and easily find and get information about the products they need. The method used in this study is to collect the data information needed in the catalogue. The results of the product catalogue design are analyzed using an ergonomic approach, including the Visual Acuity, font size, and analysis of the colour composition between the characters and the background along with their psychic effects. Visual acuity obtained is 0.013 minutes. The results of the recommended font size are smaller than the actual font size, so it means that the font size on the product catalogue website display is ideal . The results of colour analysis on the website also provide good legibility and provide a clean and calming effect.